Decreasing of hand colonization and sterility of refill antiseptic in Dr. Yap Eye Hospital, Yogyakarta - Briliana Nur Rohima; Syarah Rysty; Ulupi Rina Hapsari; Palupi Dwi Astuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Dr. Yap Eye Hospital, Yogyakarta uses aseptic gel containing 70% ethyl alcohol to refill antiseptic containers during times of antiseptic scarcity. The study aimed to evaluate the effectiveness and sterility of the refill antiseptics in reducing the number of colonization on the hands of nurses. It was a quasi-experimental using pre- and post-control groups design involving 56 nurses who used antiseptics in a bottle sterilized by plasma device (plasma bottle) compare to those washed using detergent (detergent bottle) before being refilled. Sterility tests were performed every two wk for up to two mo. Colonization pre and post hand hygiene practices were determined as an efficacy test and compared using the Mann-Whitney test in STATA 14. Antiseptic in plasma bottles remains sterile until the week8th since refilled, longer than detergent bottles (6th weeks). The pre-handrub colorizations were 0.04-16.92 CFU/cm2 and decreased significantly post-handrub to 0.00-3.08 CFU/cm2 (p<0.0001). Significant decrease pre- vs post-handrub colonization was observed in usage of detergent bottle (0.04-31.04 vs 0.00-10.48 CFU/cm2, p=0.0007). There was no significant difference in ∆ colonization for two bottles (0.40-15.76 vs 0.04-30.92 CFU/cm2, p=0.8790). In conclusion, antiseptic in the plasma bottle remains sterile longer than in the detergent bottle since refilled. Both of them are equally effective in reducing colonization after handrub activity.